Inverse T-shaped sternotomy as novel thoracoplasty for severe chest deformation and tracheal stenosis - Hirofumi Tomita; Akihiro Shimotakahara; Naoki Shimojima; Hideo Ishihama; Miki Ishikawa; Yuki Mizuno; Makoto Hashimoto; Ayano Tsukizaki; Kazuaki Miyaguni; Seiichi Hirobe (Surgical Case Reports, 2021)
Abstract Background Patients with severe motor and intellectual disabilities often suffer from tracheal stenosis due to chest deformation and brachiocephalic artery compression, which sometimes leads to serious complications, such as dying spell and tracheobrachiocephalic artery fistula. We herein described our experience of performing a novel and simple thoracoplastic procedure combined with brachiocephalic artery transection in two patients with severe chest deformation and tracheal stenosis. Case presentation The patients were a 12-year-old female with cerebral palsy due to periventricular leukomalacia and a 21-year-old male with subacute sclerosing panencephalitis stage IV in the Jabbour classification following a laryngotracheal separation. Both patients showed severe chest deformation and symptoms of airway stenosis resulting in dying spells. The sternum was laterally transected between the manubrium and the sternal body, and a manubriotomy was performed longitudinally, ending with an inverse T-shaped sternotomy. Since the clavicle and the first rib remained attached to the halves of the divided manubrium, the sternum was allowed to be left open, resulting in improvement of the mediastinal narrowing and tracheal stenosis. Postoperative computed tomography (CT) showed that the distance between the halves of the manubrium was maintained at 10–11 mm, and that the mediastinal narrowing in both patients improved; the sternocervical spine distance increased from 20 mm to 22  and 13 mm to 16 mm, respectively. The patients’ tracheal stenosis below the sternal end of the clavicle and the manubrium and respiratory symptoms improved, and the patients are currently at home in a stable condition with no chest fragility and no upper limb movement disorder 1 year after surgery. Conclusions Our observations suggested that the inverse T-shaped sternotomy combined with brachiocephalic artery transection may relieve symptoms of tracheal stenosis due to severe chest deformation in patients with severe motor and intellectual disabilities.